Expression in Escherichia coli of chemically synthesized genes for human insulin. - Goeddel, D V (1979)
Synthetic genes for human insulin A and B chains were cloned separately in plasmid pBR322. The cloned synthetic genes were then fused to an Escherichia coli beta-galactosidase gene to provide efficient transcription and translation and a stable precursor protein. The insulin peptides were cleaved from beta-galactosidase, detected by radioimmunoassay, and purified. Complete purification of the A chain and partial purification of the B chain were achieved. These products were mixed, reduced, and reoxidized. The presence of insulin was detected by radioimmunoassay.